2002
DOI: 10.1063/1.1433919
|View full text |Cite
|
Sign up to set email alerts
|

Polarity determination by atomic location by channeling-enhanced microanalysis

Abstract: In this letter, an alternative approach to determine the polarity of GaN thin films based on the atomic location by channeling-enhanced microanalysis technique is described. Theoretical calculations provide a straightforward criterion for polarity determination that is a major advantage of this method. At the Bragg position, the thickness-averaged incident electron intensity, and hence, electron induced characteristic x-ray yield, is higher on the N plane than on the Ga if the g vector of the diffraction beam … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
11
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 11 publications
0
11
0
Order By: Relevance
“…2 The polarity is closely related to the film quality such as surface morphology and electronic properties, 2,3 it is important to determine polarity of such a thin film. Many methods, such as energydispersive x-ray spectroscopy, 4 coaxial impact-collision ion scattering spectroscopy, 5 convergent beam electron diffraction, 6 high-resolution transmission electron microscopy ͑HRTEM͒, 7 and electron energy loss spectroscopy 2 have been developed for the polarity determination.…”
mentioning
confidence: 99%
“…2 The polarity is closely related to the film quality such as surface morphology and electronic properties, 2,3 it is important to determine polarity of such a thin film. Many methods, such as energydispersive x-ray spectroscopy, 4 coaxial impact-collision ion scattering spectroscopy, 5 convergent beam electron diffraction, 6 high-resolution transmission electron microscopy ͑HRTEM͒, 7 and electron energy loss spectroscopy 2 have been developed for the polarity determination.…”
mentioning
confidence: 99%
“…6 Recently, Jiang et al demonstrated the method using x-ray energy dispersion spectroscopy ͑EDS͒. 7 The polarity can be determined by comparison of two or more element-characteristic x-ray intensities, which will always enhance at one Bragg orientation, and diminish at the opposite. However, the count rate of characteristic x rays is very low because the fluorescence yield is very small.…”
mentioning
confidence: 99%
“…The direction of the cation ͑Ga͒ to the anion ͑N͒ is defined as ͓0001͔ in the real space. [1][2][3][4]7 The EELS experimental studies were carried out using a Philips CM200 field emission gun TEM equipped with a Gatan image filtering system, operated at 200 kV. The energy resolution is about 1.0 eV according to the measured full width at half maximum of the zero-loss peak.…”
mentioning
confidence: 99%
See 2 more Smart Citations